THE INFLUENCE OF CONCEPTUAL COMPETENCY ON THE WORK EFFECTIVENESS OF LEMITO SUBDISTRICT OFFICE EMPLOYEES, POHUWATO REGENCY (British Journal of Global Ecology and Sustainable Development, 2023)
Research objectives: 1. To find out and analyze the extent of the influence of conceptual competence which consists of: knowledge, skills and abilities on the work effectiveness of employees of the Lemito Subdistrict Office, Pohuwato Regency. 2 To find out and analyze the influence of the most dominant conceptual competence which consists of: knowledge, skills and abilities on the work effectiveness of employees at the Lemito Subdistrict Office, Pohuwato Regency. This research method is a case study of the work effectiveness of employees at the Lemito Subdistrict Office, Pohuwato Regency. The population of this study was 74 employees consisting of sub-district employees and officials from 8 villages. Research results 1) Taken together, the influence of conceptual competence, namely: knowledge, skills and abilities, has a significant effect on the work effectiveness and service of employees at the Lemito sub-district office, Pohuwato Regency. 2 Partially, the most dominant influence influences the work effectiveness of employees at the Lemito sub-district office, Pohuwato Regency. is Skills. The skills referred to can be the implementation of practical work procedures, special techniques, and scientific disciplines for each employee as a source of competence.